2010
DOI: 10.1038/nm.2250
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-induced S1PR1 expression is crucial for persistent STAT3 activation in tumors

Abstract: IL-6/Jak2 signaling is viewed critical for persistent Stat3 activation in cancer. However, IL-6-induced Stat3 activity is transient in normal physiology. Here we identify a mechanism important for persistent Stat3 activation in tumor cells and the tumor microenvironment. We show that sphingosine-1-phosphate receptor 1 (S1PR1), a G-protein-coupled receptor for lysophospholipid sphingosine-1-phosphate (S1P), is elevated in Stat3-positive tumors. Stat3 is a transcription factor for the S1pr1 gene. Enhanced S1pr1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
390
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(418 citation statements)
references
References 41 publications
23
390
3
2
Order By: Relevance
“…In particular, S1P1 mediated promigratory effects [31] , whereas S1P2 inhibited cell migration [32] . An increased S1P1 expression, which was recently induced by [33] . In glioblastoma and in Wilms tumor cells S1P-dependent S1P1 signaling induced cell migration and invasion [34,35] , whereas in glioblastoma and melanoma cells S1P-dependent S1P2 pathway negatively directed migration and invasion [32,36] .…”
Section: Gpcrs Activated By Bio-active Lipidsmentioning
confidence: 97%
“…In particular, S1P1 mediated promigratory effects [31] , whereas S1P2 inhibited cell migration [32] . An increased S1P1 expression, which was recently induced by [33] . In glioblastoma and in Wilms tumor cells S1P-dependent S1P1 signaling induced cell migration and invasion [34,35] , whereas in glioblastoma and melanoma cells S1P-dependent S1P2 pathway negatively directed migration and invasion [32,36] .…”
Section: Gpcrs Activated By Bio-active Lipidsmentioning
confidence: 97%
“…The level of expression (by RT-PCR) of S1P1 in S1pr1-TKPTS was 29-fold compared with pcDNA-TKPTS-transfected cells (Supplemental Figure 5, A and B), and there was no change in expression of S1P3-S1P5 or sphingosine kinases 1 and 2 (data not shown). Western blot showed a band of the correct predicted molecular weight for S1P1 (rabbit3S1P1, 1:250, clone H-60; Santa Cruz Biotechnology, Dallas, TX 51,52 ) in cytoplasmic and membrane fractions of cell lysates of S1pr1-TKPTS that was not visible in the membrane fraction after treatment of cells with 10 nM FTY720-p for 24 hours (presumably due to internalization of the receptor). S1P1 was undetectable in untransfected TKPTS cells or pcDNA-TKPTS cells (Supplemental Figure 5C).…”
Section: Stable Overexpression Of S1pr1 In Tkpts Cellsmentioning
confidence: 99%
“…132 Ablation of STAT3 in tumor-associated myeloid cells significantly reduced the RELA activity in the tumor milieu including the CD11b Ăž myeloid infiltrate. 132,133 A hypothesis was suggested that when both STAT3 and NF-kB are activated in the same cell they induce the expression of protumorigenic inflammatory signals. 120 Accordingly, continuous STAT3 activation in the tumor microenvironment (including the immune cells) selectively favored NF-kB binding to the promoters of genes containing STAT3 DNA-binding sites, Tumor microenvironment and inflammation H Roca and LK McCauley which are also associated with immunosuppression and tumorpromoting inflammation.…”
Section: Molecular Pathways Of Metastasis-promoting Inflammationmentioning
confidence: 99%
“…[138][139][140][141] An amplification loop identified in tumors links the sphingosine 1-phosphate (S1P) signaling through the S1P receptor 1 (S1PR1) and the activation of STAT3, which in turn feeds back to upregulate S1PR1. 133 This pathway results in the upregulation of S1PR1 in the tumor microenvironment leading to continuous STAT3 activation in cancer cells inducing the expression of factors that trigger the same pathway in myeloid cells. 138 This signaling allows STAT3-activated myeloid cells to invade, survive and proliferate at the distant premetastatic sites to facilitate the colonization of cancer cells at the preselected site.…”
Section: Molecular Pathways Of Metastasis-promoting Inflammationmentioning
confidence: 99%